2020
DOI: 10.1186/s12870-020-02772-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined proteomics, metabolomics and physiological analyses of rice growth and grain yield with heavy nitrogen application before and after drought

Abstract: Background Nitrogen application can effectively mitigate the damage to crop growth and yield caused by drought. However, the efficiency of heavy nitrogen application before drought (NBD) and heavy nitrogen application after drought (NAD) to regulate rice response to drought stress remains controversial. In this study, we profiled physiology, proteomics and metabolomics in rice variety Wufengyou 286 of two nitrogen management modes (NBD and NAD) to investigate their yield formation and the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…A combination of proteomics and metabolomics revealed a regulatory network in crops to abiotic stresses, such as heat ( Wang et al, 2018 ), drought ( Michaletti et al, 2018 ; Budzinski et al, 2019 ; Du et al, 2020 ), and drought–flood alternation ( Xiong et al, 2019 ). Michaletti et al (2018) revealed that total protein content decreased more severely in drought-sensitive wheat than in drought-tolerant wheat and drought stress changed the abundance of main metabolites ( Michaletti et al, 2018 ).…”
Section: Application Of Multi-omics Approaches In Crop Study At Abiot...mentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of proteomics and metabolomics revealed a regulatory network in crops to abiotic stresses, such as heat ( Wang et al, 2018 ), drought ( Michaletti et al, 2018 ; Budzinski et al, 2019 ; Du et al, 2020 ), and drought–flood alternation ( Xiong et al, 2019 ). Michaletti et al (2018) revealed that total protein content decreased more severely in drought-sensitive wheat than in drought-tolerant wheat and drought stress changed the abundance of main metabolites ( Michaletti et al, 2018 ).…”
Section: Application Of Multi-omics Approaches In Crop Study At Abiot...mentioning
confidence: 99%
“…High storage of protein content and high stable filling rate in wheat at heat stress are due to the reallocation of energy to heat protection and reserves deposition ( Wang et al, 2018 ). Du et al (2020) found that the drought response of rice was altered by nitrogen management methods as indicated by differentially expressed proteins and differential metabolites ( Du et al, 2020 ). Halosufuron-methyl (HSM) stress induced the accumulation of detoxification-related proteins and metabolites in soybean ( Li Y. et al, 2020 ).…”
Section: Application Of Multi-omics Approaches In Crop Study At Abiot...mentioning
confidence: 99%
“…The majority of the identified DAPs under drought conditions were related to photosynthesis, oxidative stress response, proteolysis, and translation of stress-responsive proteins, such as heat shock, and LEA proteins (late embryogenesis-associated proteins) sharply increased under drought stress. Du et al (2020) investigated the physiology of rice grown under two nitrogen management modes by proteomics and metabolomics approaches to investigate their yield formation and the mechanism of nitrogen regulation for drought tolerance. It was evident from the proteomic analysis that the most altered biological processes and pathways were related to the biosynthesis of primary and secondary metabolites important for the growth and metabolism of crop plants.…”
Section: Proteomicsmentioning
confidence: 99%
“…In all the 8 genotypes, 8 proteins were induced under drought stress (Hamzelou et al, 2020). A more comprehensive study by Du J. et al (2020) involved proteomics, metabolomics, and physiological analyses upon heavy nitrogen exposure before (NBD) and after drought (NAD) on rice (Du J. et al, 2020). The proteomic experiments were carried by tandem mass tagging of rice leaves subjected to NBD and NAD.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…The samples were analyzed by LC-MS-MS with the amount of qualitative protein and quantitative protein being 4254 and 3892 respectively. Upon drought exposure, NBD had higher chlorophyll content and photosynthetic rate, enhanced activities of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase, and catalase, and declined malondialdehyde (MDA) content (Du J. et al, 2020). Next, the application of multi-omics in salinity stress involves an analysis by Xu et al (2017) utilizing the techniques 2-DE and MALDI TOF (Xu et al, 2017).…”
Section: Abiotic Stressmentioning
confidence: 99%